2023
DOI: 10.1007/s10531-023-02686-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcode-based survey documents underestimated diversity and intricate phylogeographic patterns of aquatic Heteroptera in an endangered Balkan biodiversity hotspot: ancient Lake Skadar basin

Abstract: Lake Skadar with its surrounding springs, wetlands and larger affluents is among the most diverse freshwater ecosystems in the Mediterranean region and a key biodiversity/endemism hotspot in Europe. It is also highly endangered due to climate change and rapid tourism development in the area. Being abundant, diverse and mostly predatory, true aquatic bugs play an important role in the functioning of freshwater ecosystems and are used as indicators of aquatic habitat quality. Nevertheless, this taxonomic group h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
0
0
0
Order By: Relevance
“…For other Diptera, the threshold value of the intraspecific distance is 4-5% for genetically separate species of Tanytarsus (van der Wulp, 1874) (Chironominae) [60], and 5-8% for Polypedilum (Kieffer, 1912) (Chironominae) [61]. In one of the last studies on Skadar Lake, for the species Hydrometra stagnorum Linnaeus, 1758 (Heteroptera, Hydrometridae) it was shown that a high 6.1% intraspecific k2-p-distance could signify the presence of cryptic species; this requires more detailed investigation [62].…”
Section: Discussionmentioning
confidence: 99%
“…For other Diptera, the threshold value of the intraspecific distance is 4-5% for genetically separate species of Tanytarsus (van der Wulp, 1874) (Chironominae) [60], and 5-8% for Polypedilum (Kieffer, 1912) (Chironominae) [61]. In one of the last studies on Skadar Lake, for the species Hydrometra stagnorum Linnaeus, 1758 (Heteroptera, Hydrometridae) it was shown that a high 6.1% intraspecific k2-p-distance could signify the presence of cryptic species; this requires more detailed investigation [62].…”
Section: Discussionmentioning
confidence: 99%